Student contribution to the healthy campus program for supporting tuberculosis elimination by 2030: A strategic approach to public health and environmental health awareness - Elfiani (Asian Journal of Toxicology, Environmental, and Occupational Health, 2025)
strategic step in achieving national health targets. The main problem faced is the high prevalence of TB in Indonesia, especially in the productive age group, which can hinder the development of the younger generation. Method: The purpose of this study is to analyze the contribution of students in the Healthy Campus Program to support TB elimination through an educational approach, socialization, and utilization of technology. The method used in this study is a literature study by reviewing various literature, scientific articles, and relevant program reports. Findings: The results of the discussion show that students have great potential as agents of change in educating the public regarding TB prevention, early detection, and treatment. The Healthy Campus Program is a strategic forum that allows students to play an active role, for example through independent screening activities using the SOBAT TB application, healthy living campaigns, and the formation of anti-TB volunteer groups. The use of social media and collaboration with health institutions also strengthen the role of students in disseminating health information. Conclusion: The conclusion of this study confirms that the active involvement of students in TB elimination can have a significant impact on creating a healthier campus environment that is responsive to health issues. Novelty/Originality of this Study: This study offers an innovative approach by integrating the role of students as agents of change through the Healthy Campus program that utilizes the SOBAT TB application for self-screening, health education, and social media campaigns, creating a technology-based active participation model in supporting Tuberculosis elimination.